2007
DOI: 10.1128/iai.01673-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Antibodies Elicited by Two Heptavalent Pneumococcal Conjugate Vaccines in the Finnish Otitis Media Vaccine Trial

Abstract: In the Finnish Otitis Media Vaccine Trial, the now-licensed pneumococcal conjugate vaccine containing polysaccharides conjugated to protein CRM 197 (PncCRM) and the experimental pneumococcal polysaccharide-meningococcal outer membrane protein complex conjugate vaccine (PncOMPC), showed similar efficacy profiles against acute otitis media despite different antibody concentrations in sera. We now report the opsonophagocytic activities (OPA) in these sera. OPA, antibody concentration, and avidity for serotypes 6B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
1
26
1
3
Order By: Relevance
“…Previous studies have suggested that antibodies against serotype 19F have lower functionality than antibodies against the other serotypes included in 7vCRM (9,11,14,37). Despite this apparently weaker protection against serotype 19F, invasive pneumococcal disease due to serotype 19F is well controlled by vaccination with 7vCRM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that antibodies against serotype 19F have lower functionality than antibodies against the other serotypes included in 7vCRM (9,11,14,37). Despite this apparently weaker protection against serotype 19F, invasive pneumococcal disease due to serotype 19F is well controlled by vaccination with 7vCRM.…”
Section: Discussionmentioning
confidence: 99%
“…Despite moderate resistance to complement deposition, a very high concentration of serotype-specific antibodies was found here and previously (33) to be required for opsonophagocytosis of serotype 19F strains, suggesting inferior functional properties of antibodies. The data from clinical trials demonstrate a correlation of serotype-specific vaccine efficacy with opsonophagocytic activity of the antibodies (14,46). The antibody concentration required for 50% opsonophagocytic killing depends on the capsular serotype and up to five times higher antibody concentrations have been reported to be required for killing serotype 19F compared to 6B (14,33,43,46,59).…”
Section: Vol 78 2010mentioning
confidence: 96%
“…This protocol was initially developed for evaluation of the immunogenicities of pneumococcal vaccines. On the basis of a meta-analysis of the results of the various vaccine trials (3,8,12,15,19), WHO recommends the use of an antibody concentration of 0.35 g/ml as a correlate of protection if it is assessed by ELISA (29). This recommended protective concentration is identical for all serotypes.…”
mentioning
confidence: 99%